2020
DOI: 10.1016/j.eswa.2019.112995
|View full text |Cite
|
Sign up to set email alerts
|

TechNet: Technology semantic network based on patent data

Abstract: The growing developments in general semantic networks, knowledge graphs and ontology databases have motivated us to build a large-scale comprehensive semantic network of technology-related data for engineering knowledge discovery, technology search and retrieval, and artificial intelligence for engineering design and innovation. Specially, we constructed a technology semantic network (TechNet) that covers the elemental concepts in all domains of technology and their semantic associations by mining the complete… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
88
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 133 publications
(89 citation statements)
references
References 44 publications
0
88
0
1
Order By: Relevance
“…Via this procedure of repeating the phrase detection process with decreasing threshold values of T phrase , we identified phrases that appear more frequently in the first step using the higher threshold value, e.g., “autonomous vehicle”, and discovered phrases that are comparatively less frequent in the second step using the lower threshold value, e.g., “autonomous vehicle platooning”. In this study, we used the best performing thresholds (5, 2.5) found in a previous study [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Via this procedure of repeating the phrase detection process with decreasing threshold values of T phrase , we identified phrases that appear more frequently in the first step using the higher threshold value, e.g., “autonomous vehicle”, and discovered phrases that are comparatively less frequent in the second step using the lower threshold value, e.g., “autonomous vehicle platooning”. In this study, we used the best performing thresholds (5, 2.5) found in a previous study [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…This list, compared to our previous study, which identified a list of stopwords [ 31 ] (see S2 Table ) by manually reading 1,000 randomly selected sentences from the same patent text corpus, includes 26 new uninformative stopwords that the previous list did not cover. In the meantime, we also found the previous list contains other 25 stopwords, which are still deemed qualified stopwords in this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…B-Link (Shi et al, 2017) was developed using unsupervised learning by applying probability and velocity network analysis to correlate concepts retrieved from academic papers and design blogs. TechNet (Sarica et al, 2020) was derived using NLP techniques to extract terms from massive technical patent texts, as well as recent word embedding algorithms (i.e. word2vec and GloVe) to vectorise the terms and establish the semantic relations in the vector space.…”
Section: Construction Of Semantic Network For Engineering Designmentioning
confidence: 99%
“…These engineering design studies generally rely on common-sense knowledge bases, such as WordNet and ConceptNet, or language models not trained specifically for engineering. In fact, the engineers' perception of technical terms is biased and represented better by knowledge bases specifically trained on technological knowledge (Sarica et al, 2020). The growing uses of such public semantic network databases in the engineering design literature and methodological developments have motivated the development of the semantic networks based on engineering data.…”
Section: Semantic Network As Knowledge Bases For Engineering Designmentioning
confidence: 99%